The UK's sectoral system of biotechnology drug innovation: structure, networking and knowledge production - Tian, Xinxin (2009)
The drug discovery and development subsector lies at the heart of the pharmaceutical and biotechnology industry. However, previous studies have not distinguished this subsector from the industry as a whole. Little detailed analysis has looked at the fIrms that discover and develop new therapies. From a perspective of the Sectoral Systems of Innovation, this thesis aims to address this important gap in knowledge by looking at the structure, clustering, knowledge production and networking in the drug discovery and development subsector, and to stress the relevant policy implications.